THEORETICAL ASPECTS OF DESIGNING PEDAGOGICAL COOPERATION IN PREPARING FUTURE TEACHERS FOR PROFESSIONAL ACTIVITIES (Scientific journal of the Fergana State University, 2024)
In the article, the scientific-theoretical bases of designing pedagogical cooperation in preparing future teachers for professional activities, the methodical system of designing pedagogical cooperation in preparing for professional activities are studied. Also, theoretical aspects of designing pedagogical cooperation in preparing future teachers for professional activities were analyzed.